Symptom severity, self-reported adherence, and electronic pill monitoring in poorly adherent patients with bipolar disorder - Sajatovic, Martha (Bipolar Disord, 2015)
OBJECTIVES: This analysis of screening and baseline data from an ongoing trial examined self-report versus automated adherence monitoring and assessed the relationship between bipolar disorder (BD) symptoms and adherence in 104 poorly adherent individuals. METHODS: Adherence was measured with the Tablets Routine Questionnaire (TRQ) and the Medication Event Monitoring System (MEMS). Symptoms were measured with the Montgomery–Åsberg Depression Rating Scale (MADRS), the Young Mania Rating Scale (YMRS), and the Brief Psychiatric Rating Scale (BPRS). RESULTS: Mean age of the sample was 46.3 years [standard deviation (SD) = 9.41], with 72% (n = 75) women and 71% (n = 74) African American subjects. Adherence improved from screening to baseline with a mean missed drug proportion measured by TRQ of 61.43% (SD = 26.48) versus baseline mean of 46.61% (SD = 30.55). Mean proportion of missed medication using MEMS at baseline was 66.43% (SD = 30.40). Correlation between TRQ and MEMS was 0.47. Correlation between a single index drug and all BD medications was 0.95. Symptoms were generally positively correlated with TRQ (worse adherence = more severe symptoms), but in most instances was only at a trend level (p > 0.05) with the exception of correlation between baseline TRQ and MADRS and BPRS, which were positive (r = 0.20 and r = 0.21, respectively) and significant (p ≤ 0.05). CONCLUSIONS: In patients with BD, monitoring increased adherence by 15%. MEMS identified 20% more non-adherence than self-report. Using a standard procedure to identify a single index drug for adherence monitoring may be one way to assess global adherence in patients with BD receiving polypharmacy treatment. Greater BD symptom severity may be a clinical indicator to assess for adherence problems.